The Diffusion Coefficients of Different Types of Liquid Environments Into Binary Polymer Blend - Hameed, Awham M; Helal, Raghad H (Al-Nahrain Journal of Science, 2018)
In this study, unsaturated polyester resin (UPE) and Natural rubber (NR) were used to prepared binary polymer blend (UPE/ NR) with weight ratio (95/5) %. The present paper investigates the diffusion behavior of three environmental groups , the first group is different types of water included (distilled water, tap water, rain water), the second is diluted solutions with same concentration (HCl , H2SO4, NaCl) and the third is solvents (ethanol, kerosene, benzene) and study their effects through (UPE/NR) polymer blend. Consequently, a set of specimens were immersed in various types of water, solutions and solvents for different periods of time. The diffusion coefficients (Dx) of these liquids were calculated based on Fick's law. The results of a series of experimental investigations showed that the values of (Dx) of all liquids are in the range (3.95- 9.1 *10-12 m2/s) except benzene which behaves another behavior called (non- Fickian diffusion) through the same time of immersion.Keywords:polymer blends,Unsaturated polyester resin,Natural rubber,diffusion coefficient